The Impact of Hotmap - Fisher, Danyel (Microsoft, 2009)
In 2006, we released Hotmap internally at Microsoft. Hotmap illuminates how users have used Virtual Earth by visualizing the tiles that have been looked at by users. While the technical aspects and basic usage of Hotmap have been previously discussed [1][2], this paper discusses the next steps: the impact of Hotmap, the ways that Hotmap was used over the following years, and the fate of the tool three years later.
The Infovis 2009 Discovery Exhibition